Microbial occurrence at different freezing duration in speckled shrimp, Metapenaeus monoceros (Fabricius, 1798) from local markets of Dhaka city - Khan, Md Anisur Rahman; Yasmin, Tamanna; Nilla, Saima Sharif; Khan, Md Mahmudur Rahman; Rahman, Naziza; Rashid, Md Mahamud Ur; Mustafa, Md Ghulam (Dhaka University Journal of Biological Sciences, 2013)
A study was carried out at four different (0, 1, 7 and 30 days) freezing durations in regard to the microbiological incidence in speckled shrimp (Metapenaeus monoceros) from three different local markets - Ananda bazaar, New Market and Polashi bazaar of Dhaka city. The study unveiled that Ananda bazaar samples were more or less contaminated than those of others. The microbial load varied with market sources as total bacteria count (TBC), total coliform count (TCC) and faecal coliform count (FCC) were found in all the storage periods crossing the acceptable limit. Except for E. coli (EC), all the bacterial counts were significantly different (p < 0.05) in 7 and 30 days freezing durations. A significant difference (p < 0.05) was found in all freezing durations only for EC counts. After 30 days storage duration for all counts showed 101 cfu/g reduction of microbial load from every initial count. The Salmonella-Shigella (SS) and Vibrio spp. were identified in all the samples of the three markets. In case of biochemical composition, an inverse relation was found in moisture - protein and moisture - fat where the moisture content increased after 30 days freezing duration but protein and lipid contents decreased with time. This study revealed that shrimp available in local markets of Dhaka city was highly ingested with pathogenic bacteria which indicate the unhygienic condition of the market premises. Dhaka Univ. J. Biol. Sci. 22(2): 91-101, 2013 (July)